Types of Tourism Reception Environments – a Geographical Perspective - Bachvarov, Marin (Turyzm/Tourism, 2006)
The article discusses the relation between tourism and types of geographical environment (reception landscapes). There are four basic physical reception environments (coastal areas, mountain and upland areas, plains and lake districts, urban and urban fringe areas). In each of them tourism space is created in a different, distinctive way and characteristic stages and forms of tourism development can be observed. Irrespective of the differences between individual reception environments, there is a universal core relation with tourism, which we believe allows theoretical, methodological generalizations and possible solutions.